PEMANTAUAN TIMBEL (Pb) DI DAERAH, SERPONG, PUSPIPTEK DAN SEKITARNYA - Halimah Syafrul; Esrom Hamonangan; Retno Puji Lestari; Emalya Rachmawati; Lia Mulyaningsih (Jurnal Ecolab, 2007)
Pusarpedal-KLH monitored Lead (Pb) concentration in Serpong area from 2001 – 2004. The result was around 0.5-6 μg/m3 and average was 2.51 μg/m3 exceeded national ambient air quality standard (PP 41/1999), for 24 hour that is 2μg/m3 and also for annual that is 1 μg/m3. The present condition of the high concentration of Pb in Serpong area was verified by the conducted measurement at 10 (ten) sampling points at around Puspiptek area, kec. Serpong, Kec.Pagedangan Kec Pamulang, dan Kec. Gunung Sindur on January to February 2006. The result obtained was exceeded national ambient air standard at SD Setu Muncul (Pb concentration: 6.03 μg/m3), Batan Indah (Pb concentration: 3.79 μg/m3) and BSD Griya Loka (Pb concentration: 2.1 μg/m3). The Pb concentration in elementary school children blood was also monitored in Serpong and its surroundings. As result, Pb concentration in elementary school children blood Serpong elementary school children blood was ranged from 7-12 μg/dl, with average concentration; SDN Setu 01 = 12.0μg/dl, SDN Puspiptek = 9.5 μg/dl), SDN Kademangan = 7.1 μg/dl, and SDN Batan = 7.5 μg/dl. The Pb concentration in elementary school children blood in Jakarta area was ranged from 2.1 - 6.1 μg/dl. Standard specified by Center for Disease Control and Prevention (CDCP)-USA is: 10 μg/dl. The evaluations of meteorological data and emission source have been conducted, in order to understand the air pollution situation in Serpong area. Frequency distribution of wind speed and wind direction was calculated and conclude that 50-60% was calm condition, and the emission sources at Serpong and its surroundings in radius 30 s/d 40 km.